EFFECT OF DIFFERENT SHEAR WALL CONFIGURATIONS ON SEISMIC RESPONSE OF A MOMENT-RESISTING FRAME - Anshul Sud; Raghav Singh Shekhawat; Poonam Dhiman (European Scientific Journal, ESJ, 2014)
Use of shear walls in RC buildings is one of the most commonly used strategies for earthquake mitigation. To avoid torsion in buildings, shear walls must be placed symmetrically in plan. In this paper, a five-storey RC building located in seismic zone-V is considered with four shear walls. Five different configurations of shear walls viz. bare frame, shear wall symmetrically placed at exterior bays (centrally), at core and adjacently placed in exterior of the building, are considered. These frames are analysed for seismic forces to assess performance in terms of base shear, storey drift, member forces and joint displacements. The frame with shear walls at core and centrally placed at exterior bays showed significant reduction of order 29% to 83% in lateral displacement. The reduction in bending moments is approximately 70% to 85% for interior and perimeter columns respectively. Shear and axial forces in columns have reduced by 86% and 45% respectively. Based on such results, the best placement of shear walls in building plan is suggested.